An l‐shaped 4‐element monopole MIMO antenna system with enhanced isolation for mobile applications. Issue 11 (29th August 2016) - Ikram, M.; Hussain, R.; Hammi, O.; Sharawi, M. S.
ABSTRACT: In this work, a 4‐element wideband printed modified monopole based multiple‐input multiple‐output (MIMO) antenna system is presented. The proposed design is compact, low profile, and suitable to be used for wireless handheld devices in 3G and 4G LTE bands. The covered measured frequencies lie between 2017 and 2265 MHz. The proposed design is evaluated for MIMO performance metrics. A defected ground structure that is based on a combination of an array of vertical slots and one circular slot is used to enhance the isolation. The envelope correlation coefficient was <0.1889. The MIMO antenna system is built on a double layer FR‐4 substrate with height of 0.8mm and dielectric constant of 4.4. The total size of the design is 100 × 60 × 0.8 mm 3 . Good agreement between simulated and measured results is obtained. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2587–2591, 2016